Nano Coating Of Cu-O Particles On Single Slope Solar Distillation Absorber Plates - Caturwati, Ni Ketut; Dwinanto, Dwinanto; Farhan, Dhika (Universitas Sultan Ageng Tirtayasa, 2024)
Clean water is one of the basic needs for living creatures, especially humans, such as for drinking, cooking, washing, and so on. Natural sources of clean water have become increasingly rare in recent years, while the water that is available is increasingly polluted and contaminated by human and industrial activities. For this reason, various efforts are needed to process the available water into potable water that is suitable for drinking. One easy and cheap way to treat clean water is by distillation which utilizes solar radiation heat, known as solar distillation. The use of solar distillation technology generally has very low productivity, so it is necessary to develop technology so that productivity can be increased. This paper shows the effect of adding Cu-O nanoparticles to the absorber plate coating paint located at the bottom of the basin of a solar-powered distillation device to increase the productivity of clean water resulting from distillation. Variations in the concentration of Cu-O nanoparticles coated on the absorber plate are: 10%, 15% and 20% by weight of the black paint used. Experimental results show that there is an increase in efficiency of 6.66%, 16.91% and 27.93% for Cu-O concentrations in black paint of 10%, 15 % and 20% by weight respectively.